CHILD PROTECTION ACCORDING TO ISLAMIC LAW AND FORMAL LAW - Ahmad Fausi; Imanuddin Abil Fida (LPPM STAI Muhammadiyah Probolinggo, 2021)
The word protection according to the Indonesian dictionary is a shelter or things (deeds and so on) that must be protected. Then, Law No. 23 of 2002 on child protection states that protection covers activities to guarantee and protect children and their rights in order to live, grow and participate optimally in accordance with human dignity, and to obtain protection from discrimination. If parents always protect and pay attention to their children as blessings of God and protect them from actions that can damage the future of the child, then parents should be responsible to keep and protect them. As stated in Tafsir al-Qurtubi which expressed the opinion of Ibn Abas in understanding the above verse: as a form of the command to the husband to protect himself and his family from the fire. The application of the verse in everyday life is to take care of one's self by observing the rules of religion and keeping the family by calling them to worship and pray to God, so they were saved from the fire. The most important issue that is always discussed by scholars of jurisprudence is the issue of parenting (Hadhonah) in order to maintain and sustain the continuity and preservation of the life of the newborn. Hadhonah is to nurture a child who has not been able to take care of his own life by providing something for the welfare and security, taking care of something painful and dangerous, educate and building himself physically and spiritually. Children are an Almighty's grace for parents, children are also mandated and jewelry for them, as well as pride in the future, but in addition, children can also be a slandered person or a test, even become enemies for their parents. The National Legal Development Board of the Department of Law and Human Rights provides an understanding that the harmonization of law as a scientific activity for the harmonization process (balance alignment) of written law that refers to philosophical, economic, and juridical values17 As from the description above, the harmonization of Islamic law into national law is a process of harmonization and alignment of Islamic law into national law as a form of making the legal product itself. From the description above, the author sees that the study of harmonization between Islamic law and national law is an interesting study because of the position of Islamic law as one of the National Law builders. In addition, this law is one form of the legal umbrella against childcare itself. So in the glasses of the author, this law is one form of implementing Islamic law into positive law. This is the first step in integrating positively of Islamic law into positive law. Therefore, the writing of this thesis entitled Child Protection according to Islamic Law and Formal Law with Law No. 23 of 2002 on Child Protection.Keywords: child, child protection, Islamic Law, Formal Law